2011
DOI: 10.1007/s12600-011-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and pathogenicity of Fusarium oxysporum isolated from wilted rocket plants in Italy

Abstract: Thirty-six isolates of Fusarium oxysporum originated from Eruca vesicaria and Diplotaxis tenuifolia together with eight reference strains belonging to the formae speciales raphani, matthioli and conglutinans, typical on the Brassicaceae family, were tested for pathogenicity on two species of rocket plants (E. vesicaria L., syn. E. sativa, cv. 'Rucola coltivata'; and D. tenuifolia cv. 'Winter') cultivated in the glasshouse. The results showed that different isolates were slightly, moderately or highly virulent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The primers FIGS11/NPIGS-R were able to specifically amplify a DNA product from the Fo isolates that showed potential for controlling Fusarium wilt of cucumber (Table 1 and Fig 2). The variation in the intergenic spacer (IGS) region of ribosomal DNA is useful for resolving intra-specific relationships within Fo [23], [25], [26]. It has been suggested that the variation in the IGS of rDNA may have a considerable effect on development, evolution, and ecology through its effects on growth-rate regulation, resulting from the role of the IGS in the production of rRNA [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers FIGS11/NPIGS-R were able to specifically amplify a DNA product from the Fo isolates that showed potential for controlling Fusarium wilt of cucumber (Table 1 and Fig 2). The variation in the intergenic spacer (IGS) region of ribosomal DNA is useful for resolving intra-specific relationships within Fo [23], [25], [26]. It has been suggested that the variation in the IGS of rDNA may have a considerable effect on development, evolution, and ecology through its effects on growth-rate regulation, resulting from the role of the IGS in the production of rRNA [41].…”
Section: Discussionmentioning
confidence: 99%
“…The intra-species diversity of several fungi, including formae speciales and races, has been further distinguished using the PCR approach [20], [21]. Recent studies showed that the intergenic spacer (IGS) region of ribosomal DNA (rDNA) is a source of phylogenetic markers in Fo [22], [23], [24], [25], [26] and that the region amplified with the general primers FIGS11/FIGS12 is suitable for the study of populations, including relationships among the Fo isolates [22], [27]. The objectives of this study were to identify polymorphisms in the IGS region of rDNA that differentiate nonpathogenic from pathogenic Fo isolates and to develop a method to assess the efficacy of nonpathogenic Fo isolates for use as potential biocontrol agents to manage Fusarium wilt of cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts are made to replace them with molecular identification techniques to group isolates (Lievens et al, 2008;Pasquali et al, 2008). To better understand the genetic relationship between the formae speciales of F. oxysporum that have been already characterized and our isolates, it was useful to sequence the EF-1 and IGS regions (Srinivasan et al, 2012). Sequence analysis is very precise and reproducible to evaluate genetic similarity or identity, and can separate formae speciales of F. oxysporum better than RAPD, which was used in this work only to assess the similarity of the eleven FUSCIC.…”
Section: Discussionmentioning
confidence: 99%
“…The two formae speciales that affect cultivated rocket, that is, Fusarium oxysporum ff.spp. raphani and conglutinans, the first of which is more frequently detected (Garibaldi et al, 2006;Srinivasan et al, 2012), also affect other genera belonging to Brassicaceae, such as cabbage, brussel sprouts, broccoli, turnip, radish and stock (Garibaldi et al, 2006). The Fusarium wilt of lettuce and rocket are easily and frequently seed-transmitted (Gullino et al, 2014), thus suggesting the importance of preventative disease management strategies.…”
Section: Introductionmentioning
confidence: 99%